Degradation mechanisms of high capacity 18650 cells containing Si-graphite anode and nickel-rich NMC cathode. (20th February 2019) - Li, Xuemin; Colclasure, Andrew M.; Finegan, Donal P.; Ren, Dongsheng; Shi, Ying; Feng, Xuning; Cao, Lei; Yang, Yuan; Smith, Kandler
Abstract: Application of advanced anode and cathode materials in commercial lithium-ion batteries is attracting attention due to their high capacity. Silicon (Si)/graphite anodes and nickel (Ni)-rich lithium nickel manganese cobalt oxide with layered structures have been paired in commercial 18650 high energy density cells (∼270 Wh/kg). It is crucial to investigate the cell performance and the aging behavior of this commercial cell. In this study, we present commercial cell degradation mechanisms by comparing fresh and aged electrodes, including changes of crystal structure, morphology, elemental composition, and electrochemical properties. The quantitative analysis was done based on dV/dQ incremental capacity analysis of 18650 cells. To determine the amount of cyclable lithium ions (Li + ) and active material loss, the lithiation and delithiation capacity were compared for fresh and aged electrodes in half coin cells. Results showed that even with 5% (by mass) of Si added in the anode, cracks occurred across the anode leading to contact loss and thickening of the solid electrolyte interphase (SEI) layer. Additionally, the average fluorine (F) ratio of the aged anodes was higher compared to that of the fresh anodes. More severely, the F content on the Si aggregations on aged anodes increased to as high as 5 times that of the fresh anode, indicating SEI growth, especially on Si particles. Solid 7 Li nuclear magnetic resonance results showed no detectable Li metal deposition on the aged anode. On the cathode side, cracks on the primary particle interfaces contributed to cathode material loss, contact loss, and impedance rise. Therefore, Li + loss into the thickened SEI layer, particle cracking, and impedance rise are the main reasons behind cell degradation. Graphical abstract: Image 1